Object Detection and Movement Tracking Using Tubelets and Faster RCNN Algorithm with Anchor Generation - Prabu Mohandas; Jerline Sheebha Anni; Rajkumar Thanasekaran; Khairunnisa Hasikin; Muhammad Mokhzaini Azizan (Hindawi Limited, 2024)
Indexed by WOS/Scopus/ERA